Regime de informação das políticas públicas LGBTI+ no Brasil - Santos, Raimundo Nonato Ribeiro dos (2020)
It analyzes the information regime of LGBTI+ public policies in Brazil, identifying the elements that compose it (contexts, social actors, information devices, information artifacts and information actions). Based on the conceptual network of Information Science, the theoretical framework relates the concepts of public policies, information policies, information regime, gender and sexual diversity. The methodology proposes the paradigm evidentiary approach to the development of research, classifying it as qualitative and quantitative, about their approach; applied, as to its nature; descriptive, regarding its objectives; bibliographic / documentary and action research as to their procedures. Data collection was performed by brauseio, browsing, identifying and collecting data in portals and web sites of the Federal Government and state governments and other social actors in the research field, with additional information in bibliographic / documentary. We gathered the data collected in two sets, aiming at its organization, analysis and interpretation. Initially, we present a mapping of Brazilian public policies for the LGBTI+ population, at national and state levels. Next, we present a reconfiguration of the information regime model, which together with the mapping, allowed us to describe the information regime of LGBTI+ public policies. We conclude by pointing out the impact of information as a vector for inclusion, protagonism, building citizenship and reducing inequalities, which can contribute to tackling homophobia, the dominant view of gender and machismo, promoting diversity in all spheres of society, including in Information Science.